Comparison and Analysis of Timbre Fusion for Chinese and Western Musical Instruments - Liu, Jingyu; Wang, Shuang; Xiang, Yanyin; Jiang, Jian; Jiang, Yujian; Lan, Jing (Frontiers in Psychology, 2022)
Timbre fusion is the theoretical basis of instrument acoustics and Chinese and Western orchestral acoustics. At present, researches on timbre fusion are mainly focused on Western instruments, but there are few researches on timbre fusion of Chinese instruments. This paper explores the characteristics of timbre fusion of Chinese and Western instruments, focusing on the subjective attributes and objective acoustic parameters of timbre fusion of Chinese and Western instruments, and carries out a series of experiments. Firstly, a database containing 518 fusion materials of Chinese and Western instruments was constructed, which provides necessary basic data for subjective and objective analysis of timbre fusion. We designed and conducted a subjective evaluation experiment of timbre perception attributes based on method of successive categories. Through statistical processing of experimental data such as variance analysis, multidimensional preference analysis and correlation analysis, we studied the influence of time domain characteristics and instrument types on the fusion, separation, roughness and pleasant, and compared the differences between Chinese and Western instruments in these four perception attributes. The results show that fusion and separation are the most important attributes for Chinese instruments timbre, while roughness is the most important attribute for Western instruments timbre. In addition, this paper uses multiple linear regression, random forest and multilayer perceptron to construct a set of timbre fusion models for Chinese and Western instruments. The results show that these models can better predict the timbre fusion attributes. The research also found that there are some differences between the timbre fusion models for Chinese and Western instruments, which is consistent with the analysis results of subjective experimental data. The contribution of acoustic objective parameters to the fusion model is also discussed.